Can the subaltern file claims? The World Bank Inspection Panel and subaltern articulation - Ziai, Aram (Momentum Quarterly, 2016)
According to Gayatri Spivak, the problem with subaltern articulation is that the subaltern lack the 1) ability and 2) opportunity to articulate their interests, and that 3) their articulations are not ‘heard’, i.e. they have no political effect. Since its inception in 1994, the World Bank Inspection Panel has worked as a mechanism of accountability in this international organization. People negatively affected by World Bank projects are given the opportunity to file claims against the violation of social and environmental standards. While some scholars argue that the Inspection Panel has led to a democratization of global economic governance, this contribution employs an empirical case study to examine whether and to what extent it has actually provided an effective voice for the subaltern.